Port resiliency and the effects of hurricanes on port operations. (3rd February 2022) - Folkman, Dylan; Gharehgozli, Amir; Mileski, Joan; Galvao, Cassia Bomer
This paper studies the negative effects of hurricanes on port operations. Hurricanes push a large amount of sediment into the port and connecting channels, thus decreasing the water depth. As a result, larger vessels need extra time to de-ballast the water from the ballast tanks in order to reduce their draft and enter the port. Arena software is used to simulate port operations before and after a hurricane. The simulation study addresses how de-ballasting can affect the port key performance indicators. The model before a hurricane allows ships to enter the port, unload and load containers, and leave the port, while the after-hurricane model forces the large vessels to first empty their ballast tanks before entering the port. The simulation models are used to study the case of hurricane Harvey at the Port Houston. The results show that hurricanes have detrimental impacts on the port.